Evaluating the Hypoglycemic Efficacy and Quality Assurance of Ya That Opchoei Mixture - Thaweesak Juengwatanatrakul PhD; Kusuma Jitsaeng PhD; Rawiwun Kaewamatawong PhD (Journal of Evidence-Based Integrative Medicine)
Diabetes mellitus, diagnosed as Madhumeho (sweet urine) in Thai traditional medicine, is believed to stem from imbalanced life elements. Ya That Opchoei mixture (YTO), a polyherbal mixture, is used to treat its symptoms. This study assessed the hypoglycemic potential of YTO and conducted qualitative and quantitative analyses of its bioactive constituents. YTO significantly inhibited α -glucosidase at IC 50 0.05 ± 0.00 mg/mL and α -amylase activities at IC 50 0.04±mg/mL. YTO at concentrations of 2.22 mg/mL significantly increased C-peptide secretion and stimulated glucose uptake. Liquid chromatography-mass spectrometry revealed constituents from Amomum testaceum , Cinnamomum bejolghota , C. burmanii , Syzygium aromaticum , and Glycyrrhiza glabra . High-performance liquid chromatography enabled quantification of bioactive compounds, including glycyrrhizic acid, eugenol, cinnamic acid, cinnamaldehyde, and coumarin. The coumarin content in 100 mL YTO was within the tolerable daily intake set by the European Food Safety Authority. This study confirms the hypoglycemic potential of YTO and presents its quality control process for safety assurance.